Synergistic Effects of Probiotics and Autogenous Bacterin against Salmonella enterica Serovar Typhimurium Strain U288 (IPS Journal of Nutrition and Food Science, 2022)
Salmonellosis, a disease caused by pathogenic strains of Salmonella, has been reported to have an essential degree in morbidity and mortality of humans (especially farmers) and poultry resulting in low productivity. This study was undertaken to evaluate the synergistic effects of probiotics and autogenous bacterin against Salmonella enterica serovar Tyhimurium strain U288 isolated from different poultry feed collected from Orlu-west Local Government Area of Imo State. Different types of feed samples were aseptically collected and screened for the presence of Salmonella enterica serovar Typhimurium using standard microbiological techniques. The pathogenic potentials of the organism in broiler chicks were investigated by challenging the chicks orally using 0.5ml of the inoculum (108cells/ml).The protective effects of locally prepared autogenous bacterin (B), commercially prepared probiotics (P) and autogenous bacterin plus commercially prepared probiotics (BP) were investigated using in vivo technique. The study revealed significant (p
Keywords: Salmonellosis; Salmonella; Probiotics; Autogenous bacterin; Synergism